Sustainable manufacturing practice: Knowledge sharing by Malaysian SMEs - Mat Yamin, Fadhilah; Hami, Norsiah; Mohd Shafie, Shafini; Muhamad, Mohd Razali; Abdul-Aziz, Shahrun Nizam (ExcelingTech Publishers, 2020)
Sustainable manufacturing has been widely studied and practise among manufacturing company around the world. This approach is one of the best approaches to reduce the environmental impact that produce during the manufacturing process. In Malaysia, this approach has been implemented in several SMEs company. This article will present four case studies that have been conducted on four SME company in Malaysia that had implemented SMP. The four companies were selected to share their knowledge and experience on the implementation, best practice and sustainability performance. The findings show that SMP has been well practice by those companies. All companies’ emphasis on reducing environmental and social issues by implementing a number of sustainable manufacturing practices such as cleaner production, eco-efficiency, employee-oriented sustainable practices, supplier-oriented sustainable practices, and customer-oriented sustainable practices. This finding can be used as a guideline for Malaysian SMEs in implementing the sustainable manufacturing practices in their organization